Evaluation of potential androgenic and antiandrogenic activities of pure cyanotoxins (microcystin-LR and cylindrospermopsin) using the hershberger bioassay (OECD TG 441) - Antonio Casas-Rodríguez; Nahum Ayala-Soldado; Ana María Cameán; Angeles Jos (Ecotoxicology and Environmental Safety, 2025)
Cyanotoxins, produced by cyanobacteria, pose significant health risks due to their acute and chronic toxic effects on humans and animals. Among these toxins, microcystins (MCs) and cylindrospermopsin (CYN) have shown potential as endocrine disruptors, as they affect hormonal regulation and reproductive processes, particularly through interference with key hormonal signalling pathways. In this study, the Hershberger bioassay was employed to assess the (anti)androgenic effects of MC-LR and CYN (22.5–90 μg/kg b.w./day) in castrated male rats, following the OECD 441. The bioassay measured changes in the weights of five androgen-dependent accessory sex tissues and additionally serum hormone levels, including testosterone (T), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and thyroid hormones. In the androgenic assay, MC-LR led to an increase in the seminal vesicle weight at the lowest dose. In contrast, in the antagonist assay, some significant differences were found. Among others, MC-LR reduced ventral prostate weight, while CYN showed similar effects on the glans penis. However, following the criteria of OECD 441, both cyanotoxins did not exhibit any androgenic or antiandrogenic activities under the conditions assayed. However, some changes in hormone levels were found. Thus, in the agonist assay, LH and FSH levels were elevated at 90 μg/kg b.w./day with both toxins, and CYN also increased LH values even at 22.5 μg/kg b.w./day. In the antagonist experiment, lower T levels were found in all MC-LR groups compared to the negative control. This study highlights the need for further investigation into the endocrine-disrupting properties of cyanotoxins, to fully understand their implications for wildlife and human health.